Pengaruh Karakteristik Sistem Informasi Akuntansi Manajemen: Broad Scope, Timeliness, Aggregated, Dan Integrated Terhadap Kinerja Manajerial Umkm. (Studi Pada Umkm Di Desa Wedoro, Kab. Sidoarjo) - Handayani, Susi; Hariyati, Hariyati (AKRUAL: JURNAL AKUNTANSI, 2014)
AbstractSMEs need information systems that are reliable and competent entrepreneurial personality that will have an impact on managerial performance. Information reliable accounting system according Chenhall and Morris (1986) is one that has the characteristics of broad scope, timeliness, aggregation and integration. Information management accounting system that is broad scope is information that attention focus, quantification, and time horizon. Timeliness dimension has two sub dimensions, namely the frequency of reporting and speed of reporting. Dimensions aggregate is a summary of information by function, time periods, and the decision model. Integrated information reflects the lack of coordination between segments of one and the other subunits within the organization. This research is quantitative. This study uses analysis of causal relationships, that is how one variable affects changes in other variables. To analyze the data, this study uses analysis of Structural Equation Modeling (SEM) approach Partial Least Square (PLS).In data processing using software Warp PLS. The results showed that the Accounting Information Systems Management is broadscope, timeliness, integrated, and the aggregate effect on Managerial Performance is measured using an instrument of self-rating which is reflected in four indicators, namely increased revenue, cost savings, improved customer satisfaction and increased asset utilization. This shows that although SMEs are the type of business that is not great, but still requires a wide range of information, timely, integrated and comprehensive that can assist managers in making informed decisions that impact the increase managerial performance related to efficiency-related costs but still consider satisfaction customers thus increasing the income of the SMEs in environmental conditions of uncertainty.Â Keywords: SME, SIAM characteristics, Managerial Performance